Isu-isu Strategik dan Implementasinya dalam Lembaga Pendidikan Islam - Faizin, Husnul (MASALIQ, 2023)
The focus of this article is to describe strategic issues and their implementation in Islamic educational institutions. The role of Islamic educational institutions in improving education is very strategic because the aim of education is basically to humanize humans, or to elevate human dignity or "human dignity". Education in Islam emphasizes the formation of human character who has noble character. With this noble moral character education, the goal of education which in Ki Hajar Dewantara's thought is "to liberate the life and life of the child, physically and mentally" can be implemented in the current independent learning curriculum paradigm. The focus of the strategic issues in this discussion are: (1) Islamic Education Orientation; (2) Learning Method Approach; (3) Professionalism and Quality of Human Resources; and (4) Education Costs. Implementation is a series of actions carried out by various actors implementing the policy with supporting means based on predetermined rules to achieve the stated goals. Turning strategic issues into action and results is a strategic step for the leadership of Islamic education institutions in transforming their institutions or organizations so that they have competitive capabilities, creating opportunities for educational services now and in the future.